2003
DOI: 10.1007/s00213-002-1242-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette nicotine content and smoking pace on subsequent craving and smoking

Abstract: The sensory cues associated with smoking suppressed craving ratings regardless of the smoking pace or nicotine content. Only at high doses did nicotine levels play an additional role in acutely suppressing smoking behavior. Small elevations in craving ratings were associated with choices to smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 35 publications
4
59
0
Order By: Relevance
“…A recent study suggested that the NMR might influence smoking behavior; smokers with higher NMR had greater puff volumes and increased levels of carcinogen biomarker (Strasser et al, 2011). These findings are consistent with previous studies indicating that smokers maintain plasma nicotine levels by adjusting their smoking behavior (Benowitz et al, 1998;Dallery et al, 2003); those with more rapid nicotine clearance would be expected to have greater nicotine intake than those with slower disposition.…”
Section: Introductionsupporting
confidence: 83%
“…A recent study suggested that the NMR might influence smoking behavior; smokers with higher NMR had greater puff volumes and increased levels of carcinogen biomarker (Strasser et al, 2011). These findings are consistent with previous studies indicating that smokers maintain plasma nicotine levels by adjusting their smoking behavior (Benowitz et al, 1998;Dallery et al, 2003); those with more rapid nicotine clearance would be expected to have greater nicotine intake than those with slower disposition.…”
Section: Introductionsupporting
confidence: 83%
“…In contrast, MEC administration precipitates nicotine withdrawal in nicotine-dependent rodents (Hildebrand et al, 1997;Malin et al, 1994). The finding that MEC did not alter craving and withdrawal suggests that other factors besides nicotine (e.g., tar) may play a role in these subjective effects of cigarette smoking (Dallery et al, 2003;Rose and Behm, 2004).…”
Section: Effect Of Mec Pre-treatment On Smoking Indices and Psychiatrmentioning
confidence: 96%
“…receiving cues alone) produces comparable levels of smoke intake, satisfaction, and reduction of craving and withdrawal as smoking nicotine-containing cigarettes (i.e. cues plus nicotine) (Gross et al 1997;Shahan et al 1999;Rose et al 2000;Shahan et al 2001;Dallery et al 2003). Similarly, the removal of visual and olfactory cues associated with cigarettes reduce overall measures of reinforcement derived from smoking ).…”
Section: Implications For Smokingmentioning
confidence: 99%